NEW PREPARATION PROCESS OF RESOLE RESIN WITH ACTIVATED KRAFT LIGNIN - VERDEL, Nada; BUKOVEC, Peter; IBRET, Slavko; IBRET, Nina (2024)
The subject of the invention is a novel process for the preparation of resole resin with activated Kraft lignin, wherein the lignin activation reaction is carried out in a first step and the synthesis of a new lignin-containing resole resin is carried out in a second step, all in the same reactor. A proportion of phenol is replaced by lignin, thus reducing the use of phenol as a feedstock, and the resole resin synthesised has a low molar mass and lower tetradimer values than existing resole resins used as binders in the manufacture of thermally insulating glass wool and rock wool. The new process for the preparation of resole resin with activated Kraft lignin increases the resin's unlimited solubility and stability up to 30 days. When using the resole resin according to the present invention as a binder for a thermal insulation panel, lower formaldehyde and phenol emissions are demonstrated.